The Management of Clinical Varicocele: Robotic Surgery Approach - Napolitano, Luigi; Pandolfo, Savio Domenico; Aveta, Achille; Cirigliano, Lorenzo; Martino, Raffaele; Mattiello, Gennaro; Celentano, Giuseppe; Barone, Biagio; Rosati, Claudia; La Rocca, Roberto; Spena, Gianluca; Spirito, Lorenzo (Frontiers in Reproductive Health, 2022)
Varicocele is a pathologic dilation of the testicular veins within the spermatic cord. Varicocele is considered the most common problem in reproductive medicine practice. It is identified in 15% of healthy men and up to 35% of men with primary infertility. The exact pathophysiology of varicoceles is not very well understood, and several theories have been proposed to explain it. Varicocele can impair sperm quality and fertility via various mechanisms: reflux of adrenal metabolites, increased testicular hypoxia, oxidative stress, and increased testicular temperature have been proposed. Several studies have reported the significant benefits on semen parameters with the surgical treatment of varicocele: reducing oxidatively induced sperm DNA damage and potentially improving fertility. Varicocele repair should be offered as a part of treatment option for male partners of infertile couples presenting with palpable varicoceles. Nowadays, there are several surgical approaches available for the treatment of varicocele, such as the retroperitoneal approach, inguinal approach, and the subinguinal approach. The subinguinal microscopic approach offers the best outcomes, such as shorter hospital stays, preservation of the testicular arteries and lymphatics, least number of postoperative complications, recurrence, and a higher number of pregnancies. Currently robotic-assisted laparoscopic surgery is widely adopted in urology and surgeons began to explore the potential applications of the robotic platform to male infertility microsurgical operations. Robotic approach offers many advantages: elimination of tremor, retraction with third arm, high quality, 3-dimensional visualization and surgeon ergonomics, all contributing to the precision of surgery.